Nuclear to Cytoplasmic Transport Is a Druggable Dependency in HDAC7‐driven Small Cell Lung Cancer - Tingting Qin; Jingya Wang; Jian Wang; Qingwu Du; Liuchun Wang; Hailin Liu; Wenting Liu; Xueyang Li; Yantao Jiang; Qi Xu; Junjie Yu; Huiyan Liu; et al. (Advanced Science)
Abstract Immunotherapy has gained approval for use in small cell lung cancer (SCLC), yet only a subset of patients (10–20%) experience meaningful benefits, underscoring the urgent need for more effective therapeutic approaches. This work discovers a distinct HDAC7‐high SCLC phenotype characterized by enhanced proliferative potential, which recurs across various subtypes and serves as a predictor of poorer survival outcomes. By analyzing public datasets, this work finds a strong correlation between c‐Myc and HDAC7. RNA sequencing and cellular experiments show that XPO1 is a key regulator in the HDAC7/c‐Myc axis. HDAC7 promotes β‐catenin deacetylation, phosphorylation modulation, nuclear translocation, and formation of the β‐catenin/TCF/LEF1 complex, which binds to c‐Myc and XPO1 promoters. Activation of the HDAC7/β‐catenin pathway upregulates c‐Myc and XPO1 expression, while c‐Myc also boosts XPO1 expression. Given the difficulty in targeting c‐Myc directly, this work tests selinexor and vorinostat in SCLC xenograft models, with selinexor showing superior results. High HDAC7 expression is linked to increased SCLC proliferation, poorer prognosis, and enhanced sensitivity to selinexor in SCLC cell lines and organoid models. Collectively, this work uncovers a novel HDAC7/c‐Myc/XPO1 signaling axis that promotes SCLC progression, suggesting that HDAC7 may warrant further investigation as a potential biomarker for assessing selinexor sensitivity in SCLC patients.